Modeling using magnetic dipole moment principle and orientation sensing of an electromagnetic spherical actuator - Lim, Chee Kian (2008)
In this work, an electromagnetic MDOF spherical actuator is proposed. The underlying principle in creating MDOF motion is by electromechanical torque generated between the rotor and stator poles. This dexterous drive can achieve 3-DOF motion within a compact rigid joint. The design is configurable and extremely simple to assemble. A torque model based on the principle of magnetic dipole moment was formulated for this class of spherical actuators. This novel approach not only allows for direct and inverse correlation with the input current and output torque in three-dimensional space, but also provides an insight into the directional determination of the motion generating torque. A prerequisite of this torque model requires the knowledge of the magnetic field distribution within the region of interest. Therefore, an analytical magnetic field model was also formulated using elliptical integrals for the computation of the magnetic field. This analytical model provides an efficient and accurate description of the magnetic field as compared to the conventional numerical method. A novel orientation sensing methodology for spherical actuator is also proposed in this thesis. By exploiting axial-symmetric magnetic field incorporated within the prototype, the rotor orientation can be ascertained by the use of Hall sensors.